Telecommunication in healthcare for a better coordination between hospitals and GP's routine application of the "ISAR-Telematics" project. - Beuscart, R. (IEEE Transactions on information technology in biomedicine)
With the development of new information and communication technologies, the nature of data exchange between healthcare professionals is modified by the use of telematics tools. With the implementation of the "Reseau Sante Social" of the smart cards CPS and Sesam-Vitale, hospitals and private clinics are installing their hospital information systems, while general practitioners are computing their patient records. The environment is therefore suitable for the installation and diffusion of telematics services, allowing a better exchange of information between the physicians of a geographical sector. The RITHME intercommunication platform was developed in the ISAR-Telematics and IRISI European projects. It ensures several communication functions, such as movements of patients (in/out/inside) the hospital, management and mailing of letters and reports, specific information on prescribed treatments, or data concerning the hospital structure. This platform is tested in the town of Armentieres in the large city of Lille (North of France). It is being routinely used to accelerate and secure data exchanges between all the physicians working in this area.